Jejak Historis Gereja Nestorian di Nusantara dan Dampaknya pada Ekspansi Kekristenan Kawasan Asia - Rikias Gulo; Malik Bambangan (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This article explores the role of the Nestorian Church in spreading Christianity throughout Asia and examines its possible presence in the Indonesian archipelago. Using a qualitative-historical approach and content analysis of primary and secondary sources, this study highlights the Nestorians' contributions in China since the 7th century, particularly in education and healthcare. While their presence in Indonesia remains debated, evidence such as activity in the port of Barus suggests they introduced Christianity through trade networks. However, their influence was curtailed by political shifts, the rise of Islam, and limited socio-political support. This study underscores the significance of the East Syrian tradition in shaping Asian Christian identity and calls for deeper inquiry into Nestorian traces in Southeast Asia. The article enriches the discourse on Asian Christian history by presenting a fresh perspective on cross-cultural faith transmission.